2001
DOI: 10.3184/030823401103168280
|View full text |Cite
|
Sign up to set email alerts
|

Zn Mediated Transesterification of β-Ketoesters

Abstract: Methyl/ethyl β-ketoesters when treated with various alcohols along with catalytic amount of Zn dust in refluxing toluene undergo smooth transesterification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 6 publications
(2 reference statements)
0
16
0
Order By: Relevance
“…[10][11][12][13] One of the predominantly employed strategies for the synthesis of coumarins is based on the Knoevenagel condensation of salicyl aldehydes and active methylene compounds. Besides the use of aldehydes, [14,15] there are some reports on the use of 2-hydroxyacetophenones [16] for the synthesis of 4-methylcoumarins [17] and on the use of 2-hydroxybenzophenones for the synthesis of 3,4-diphenylcoumarins by condensation with phenylacetic acids, [18] but no reports on the use of 2-4130 intramolecular lactonization, and decarboxylation reactions. The method can be applied to a broad scope of neoflavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] One of the predominantly employed strategies for the synthesis of coumarins is based on the Knoevenagel condensation of salicyl aldehydes and active methylene compounds. Besides the use of aldehydes, [14,15] there are some reports on the use of 2-hydroxyacetophenones [16] for the synthesis of 4-methylcoumarins [17] and on the use of 2-hydroxybenzophenones for the synthesis of 3,4-diphenylcoumarins by condensation with phenylacetic acids, [18] but no reports on the use of 2-4130 intramolecular lactonization, and decarboxylation reactions. The method can be applied to a broad scope of neoflavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…Gratifyingly, the yield of 3a increased significantly when base was added to the reaction system (entry 6). Some electron-withdrawing groups such as F and CN gave slightly lower yields (entries [12][13]. To our delight, 3a was obtained in good yield (entry 9) even without adding PTC, which demonstrated that the PTC was not crucial for the model reaction (entries 9-10).…”
Section: Resultsmentioning
confidence: 87%
“…H NMR (400 MHz, CDCl 3 ): δ = 7.48-7.39 (m, 2 H), 7.28 (d, J = 8.0 Hz, 2 H), 4.52 (s, 2 H),3.55 (s, 3 H),3.35 (s, 3 H) ppm 13. C NMR (100 MHz, CDCl 3 ): δ = 196.2, 135.7, 131.6, 131.0, 121.3, 45.5, 41.6, 41.5 ppm.…”
mentioning
confidence: 99%
“…13−16 The reaction is catalyzed by sodium hydroxide, 14 clays, 15 or lithium salts. 16 A solid-phase approach has also been described. 17 Our laboratory has been engaged in the exploration of practical green chemistry that eliminates or minimizes the use of volatile solvents that are dangerous to human life and the environment.…”
Section: Introductionmentioning
confidence: 99%